DESIGN OF COMPUTER GRAPHICS ON THE BASIS OF FRACTAL INFORMATION MODEL - Qayumova G. A. (Galaxy International Interdisciplinary Research Journal, 2022)
The article describes the application of the principle of resonant interaction of fractal pedagogy in the design of the subject "Computer Graphics" and the methodological basis for the fractal organization of personal and professional self-development of teachers and students in improving the modern educational process. The development of a classification of fractals is given.